Possible fine-tuning of methane activation toward C2 oxygenates by 3d-transition metal-ions doped nano-ceria-zirconia - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Mhamane, Nitin B.; Marelli, Udaya Kiran; Kumar, Dharmesh; Gopinath, Chinnakonda S. (Inorganic Chemistry, 2022)
In this work, we demonstrate a simple sol-gel technique to prepare metal-ion(s)-doped ceria-zirconia solid solution for efficient catalytic methane activation. The cation -depicting formula units are Ce0.80Zr0.20 (CZ), Ce0.79Zr0.20M0.01 (CZM), and Ce0.79Zr0.20M0.005M10.005 (CZMM1) (M and M1 = V, Mn, Fe, Co, and Cu), employed for undoped, mono-metal-ion -doped, and bi-metal-ion-doped solid solutions, respectively. Methane activation with Mn, Fe, Cu mono-metal-ion-doped CZ favors the C1 product, while CZCo assists C-C coupling with the formation of acetaldehyde. On the other hand, the Co-and Fe -doped bi-metal-ion combination catalyst (CZCoFe) shows significant ethanol but predominant formic acid formation. This is further promoted by the Co + V bi-metal-ion combination (CZCoV) catalyst, and it shows ethanol as the major product along with methyl hydrogen peroxide, methanol, and formic acid as minor products. An impressive ethanol yield of 93 mu mol/g h with 76% selectivity obtained with the CZCoV catalyst is at par with that obtained with noble-metal-based catalysts under comparable reaction conditions. When Co and V content was increased two and four times from 0.005 to 0.01 and 0.02, ethanol yield increased at the expense of formic acid. The 213 mu mol/g h ethanol yield (86% selectivity) observed with Ce0.76Zr0.20Co0.02V0.02 is probably the highest observed. The partial oxidation of CH4 in Co-based bi-metal combinations (Co + V or Co + Fe) suggests the synergistic effect of doped metal ions owing to the heterogeneous near -neighbor environment. The present results are attributed to the surface heterogeneity between the host and the dopants, which selectively promotes methane activation as well as C-C coupling. This indicates a large scope to tune the activity of partial oxidation of methane and product selectivity with different metal-ion(s) combinations.

Oxidative and selective C-C cleavage of glycerol to glycolaldehyde with atom-like Cu on Cu-TiO2: photocatalytic water reduction with concurrent glycerol oxidation in sunlight - Bajpai, Himanshu; Nivedhitha, Thazhath R.; Dais, Elsa; Kanungo, Subhashree S.; Gopinath, Chinnakonda S. (Journal of Catalysis, 2024)
Concurrent consumption of electrons and holes for the conversion of a biomass component to value added products represents a highly efficient and sustainable approach towards utilizing renewable energy, but difficult to achieve. The integration of hydrogen production with glycerol oxidation presents a novel and sustainable approach towards achieving a circular economy. In the current study, integration of atom-like Cu-clusters onto TiO2 substrate has been achieved using a facile photo-deposition technique (TC-PDO). Also, novel synthetic approaches have been employed to augment the surface coverage of Cu on TiO2 with atom-like clusters of Cu, either by borohydride treatment on TiO2 followed by Cu-deposition (TC-200) or oxygen-vacancy creation by UV illumination followed by Cu-deposition (TC-PDO). Increased dispersion and enhanced electronic integration of Cu with TiO2 lead to a corresponding increase in the efficiency of photocatalytic hydrogen evolution (13.8 mmol/h.g for TC-PDO at pH 9). Several atom-like Cu integrated with each TiO2 particle acts as photocatalytic reactor, and the same enhances electron-hole separation as well as activity. Sustainable aspect was also studied for TC-PDO up to 25 h at pH 9. Concurrently, glycerol oxidation displays the highest selectivity to C2 product (glycolaldehyde with 70 %) with a C-C cleavage. The investigation of this process holds significant potential for the extensive and simultaneous exploitation of electrons and holes in order to achieve water splitting and glycerol oxidation towards selective value-added products formation.
Keywords: C -C Cleavage; Glycerol; nanotechnology; Photo -deposition; solar energy conversion

Utilizing nature's endowment: artificial leaf concept for methane activation to C-C coupled ethanol or ethylene - Kanungo, Subhashree S.; Mishra, Abhaya Kumar; Avani, Mangaladasan J.; Bajpai, Himanshu; Salgaonkar, Kranti N.; Javaregowda, Bharathkumar H.; Gopinath, Chinnakonda S. (Sustainable Energy & Fuels, 2025)
Methane activation (MA) to platform chemicals under ambient conditions still remains an open challenge to be fully realised. The present work shows the fabrication of CeVO4 quantum dots (CV-QDs) by a bottom-up approach; they are assembled from Ce3+ and metavanadate ions, and structurally and electronically integrated into the micro-/meso-pores of TiO2 (CV-QD-TiO2 (CVT)), demonstrating the conversion of MA to ethanol/ethylene by visible light-driven photocatalysis. CV-QDs in confined pores modify the quantum confinement effects and are characterized by physicochemical methods. The current synthetic strategy is potentially scalable and results in sub-quadrillion heterojunctions in a 1 mg CVT photoanode spread over 1 cm2. MA with CVT under one-sun conditions demonstrates similar to 100% selectivity to ethanol, yielding 4.36 mu mol h-1 cm-2, with a solar-to-fuel efficiency (STFE) of 0.56. Further, by employing a co-catalyst, significant STFE (5.08) and yield (39.5 mu mol h-1 cm-2) are achieved selectively towards ethylene. A deliberate addition of methanol increases the rate of ethanol production by 17.2 times, indicating that the methyl-methoxy interaction is the origin of C-C coupling. Weight is normalized to a gram of CV-QDs in a large area CVT photoanode to yield 109 mmol h-1 gCV-QD-1 of ethanol and 988 mmol h-1 gCV-QD-1 of ethylene. Enhanced activity and selectivity towards the C2-product is attributed to band-edge modulation and trillions of heterojunctions, which in turn facilitate charge separation and charge transfer for effective charge utilisation at redox sites.